Comparison of GPR and unilateral NMR for water content measurements in a laboratory scale experiment. Issue 2 (1st October 2012) - Ferrara, C.; Di Tullio, V.; Barone, P.M.; Mattei, E.; Lauro, S.E.; Proietti, N.; Capitani, D.; Pettinelli, E.
ABSTRACT: Several factors affect antenna‐soil coupling in a Ground Penetrating Radar (GPR) survey, like surface roughness, lithology, lateral heterogeneities, vegetation, antenna height from the surface and water content. Among them, lithology and water content have a direct effect on the bulk electromagnetic properties of the material under investigation. It has been recently pointed out that the wavelet of the early‐time portion of a radar signal is correlated to the shallow subsurface dielectric properties of a material. This result indicates that some information on such properties can be directly extracted from the analysis of GPR early‐time traces. In the present paper, we use the early‐time GPR signal, in terms of average envelope amplitude computed on the first half‐cycle, to map the near‐surface (few centimetres) lateral distribution of dielectric parameters, induced by changing the shallow water content on a concrete slab. This controlled experiment was specifically designed to study the effect of water content variations on antenna‐material coupling, minimizing the influence of both surface roughness and heterogeneity. The quantitative control of the water in the shallow portion of the slab is performed by using a portable unilateral Nuclear Magnetic Resonance (NMR) sensor, which is able to determine the water content in the material on the basis of the measured proton density. The results show a matching pattern of the physical parameters measured with the two different techniques and a very high degree of linear correlation ( r = 0.97) between the radar early‐time signal average amplitude and the intensity of the NMR signal, which is proportional to the proton density, i.e., to the water content. This experiment suggests that the early‐time approach could be used as a fast and high‐ spatial resolution tool for qualitatively mapping water content lateral variations in a porous material at shallow depth, using a ground‐coupled single‐offset antenna configuration and that a quantitative evaluation of the moisture content would require a calibration procedure.